Ritual in its own right : exploring the dynamics of transformation - Lindquist, Galina; Handelman, Don (Berghahn Books, 2013)
Historically, canonic studies of ritual have discussed and explained ritual organization, action, and transformation primarily as representations of broader cultural and social orders. In the present, as in the past, less attention is given to the power of ritual to organize and effect transformation through its own dynamics. Breaking with convention, the contributors to this volume were asked to discuss ritual first and foremost in relation to itself, in its own right, and only then in relation to its socio-cultural context. The results attest to the variable capacities of rites to effect tr.